(3BjGJ CMcGe GdEQOHjdjs - (3GdCQOHjdj, CMeO Hf eMeO, J (B993 (3g`s ((3EHQGgje Hf MSjf Ydjs)
(3ChdgG (B:s
... (3hGdbhd aj Pdc Cf Gddg SHMGfg fOH Edi GdGSJfHGW hChVM GdSHjd Edjg heOM CbhGeG Ydjg abGd dYdeg GdPjf jSJfHWhfg efge hPe BNQjf Ydi JQc JOHjQg hGdGVQGH Yf GdJacjQ ajg abGd (B...s
(3BNQgG (B:s
.. (3acGf SHH JQc gPg GdBjI aj BjGJ GdCMcGe aj cfR GdYQaGf SHH GdfRhd hchfgG ebUhQI Ydjge ceG aYdg aj (B... (3Ke Ydi JbOjQ GdJNUU CjVG dG jHYO GdJYeje dage GdYdI ajSJNQL GdHGbj aJCed(B.s
(3JHUQI GdYfhGf (B:s
(3hoPcQ YfhGfg aj GdNGJeI (B((3fhGbU BjGJ GdCMcGe (B) (3haj bjO (B( (3RHOI GdHjGf aj HQGgjf CMcGe GdbQBf(B)s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, ddRQcdj (B1/ 234s
(3GjVGM Gdecfhf (B1\609s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs